2006
DOI: 10.1073/pnas.0510750103
|View full text |Cite|
|
Sign up to set email alerts
|

Defective cerebellar response to mitogenic Hedgehog signaling in Down's syndrome mice

Abstract: Trisomy 21 is the cause of Down's syndrome (DS) which is characterized by a number of phenotypes, including a brain which is small and hypocellular compared to that of euploid individuals. The cerebellum is disproportionately reduced. Ts65Dn mice are trisomic for orthologs of about half of the genes on human chromosome 21 and provide a genetic model for DS. These mice display a number of developmental anomalies analogous to those in DS, including a small cerebellum with a significantly decreased number of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
231
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 193 publications
(257 citation statements)
references
References 34 publications
22
231
0
2
Order By: Relevance
“…146,147 The most intensively studied mouse model of DS is the Ts65Dn line, 148 which summarizes the main hallmarks of the DS phenotype, including characteristic craniofacial abnormalities, impaired spatial and non-spatial learning abilities and attention deficits. [149][150][151][152][153][154] At the cellular level, Ts65Dn mice have a reduced number of hippocampal and cerebellar neurons, 155,156 impaired neurogenesis in the dentate gyrus of the hippocampus in both young and aged adults 157,158 and a prominent reduction in dendritic branching in several brain regions, accompanied by alterations in spine size and shape. 159 It is noteworthy that DS is also associated with reduced hippocampal neurogenesis 160 and volume 161 in humans.…”
Section: Impact Of Ee On the Brain L Baroncelli Et Almentioning
confidence: 99%
“…146,147 The most intensively studied mouse model of DS is the Ts65Dn line, 148 which summarizes the main hallmarks of the DS phenotype, including characteristic craniofacial abnormalities, impaired spatial and non-spatial learning abilities and attention deficits. [149][150][151][152][153][154] At the cellular level, Ts65Dn mice have a reduced number of hippocampal and cerebellar neurons, 155,156 impaired neurogenesis in the dentate gyrus of the hippocampus in both young and aged adults 157,158 and a prominent reduction in dendritic branching in several brain regions, accompanied by alterations in spine size and shape. 159 It is noteworthy that DS is also associated with reduced hippocampal neurogenesis 160 and volume 161 in humans.…”
Section: Impact Of Ee On the Brain L Baroncelli Et Almentioning
confidence: 99%
“…Cerebellar granule cell precursors, 5 precursors from the neural crest 43 and from the SVZ 13 of trisomic mice exhibit a significant deficit in the Shh-induced mitogenic response. We have previously shown that this defect is related to an increased expression of Ptch1.…”
Section: Dysregulation Of Ptch1 Expression May Be a Commonmentioning
confidence: 99%
“…The DS brain is characteristically small, and accumulating evidence in human fetuses with DS and DS mouse models clearly shows that this defect is due to widespread neurogenesis impairment that can be traced back to very early developmental stages. [2][3][4][5][6][7] Consequently, neurogenesis defects leading to brain hypocellularity appear to be a major determinant of cognitive disability in DS.…”
mentioning
confidence: 99%
“…Also, as in humans with Down syndrome (cf. Shapiro, 2001), the volume of the cerebellum of Ts65Dn mice is reduced, with decreased numbers of both granule and Purkinje cells perhaps resulting from dysfunctions of cell signaling mechanisms during development (Olson et al, 2004;Roper et al, 2006). Thus, understanding of the neural and cognitive phenotypic differences between partial trisomy mice and diploid mice will require assessments of many variables across age.…”
Section: General Conclusionmentioning
confidence: 99%